Efficient 23Na triple‐quantum signal imaging on clinical scanners: Cartesian imaging of single and triple‐quantum 23Na (CRISTINA). Issue 5 (28th May 2020) - Hoesl, Michaela A. U.; Schad, Lothar R.; Rapacchi, Stanislas
Abstract : Purpose: To capture the multiquantum coherence (MQC) 23 Na signal. Different phase‐cycling options and sequences are compared in a unified theoretical layout, and a novel sequence is developed. Methods: An open source simulation overview is provided with graphical explanations to facilitate MQC understanding and access to techniques. Biases such as B0 inhomogeneity and stimulated echo signal were simulated for 4 different phase‐cycling options previously described. Considerations for efficiency and accuracy lead to the implementation of a 2D Cartesian single and triple quantum imaging of sodium (CRISTINA) sequence employing two 6‐step cycles in combination with a multi‐echo readout. CRISTINA was compared to simultaneous single‐quantum and triple‐quantum‐filtered MRI of sodium (SISTINA) under strong static magnetic gradient. CRISTINA capabilities were assessed on 8 × 60 mL, 0% to 5% agarose phantom with 50 to 154 mM 23 Na concentration at 7 T. CRISTINA was demonstrated subsequently in vivo in the brain. Results: Simulation of B0 inhomogeneity showed severe signal dropout, which can lead to erroneous MQC measurement. Stimulated echo signal was highest at the time of triple‐quantum coherences signal maximum. However, stimulated echo signal is separated by Fourier Transform as an offset and did not interfere with MQC signals. The multi‐echo readout enabled capturing both single‐quantum coherences and triple‐quantum coherences signal evolution at once. Signal combination of 2 phase‐cycles with a corresponding B0 map was found to recover the signal optimally. Experimental results confirm and complement the simulations. Conclusion: Considerations for efficient MQC measurements, most importantly avoiding B0 signal loss, led to the design of CRISTINA. CRISTINA captures triple‐quantum coherences and single‐quantum coherences signal evolution to provide complete sodium signal characterization including T 2 ∗ fast, T 2 ∗ slow, MQC amplitudes, and sodium concentration.